2006
DOI: 10.1038/sj.pcan.4500856
|View full text |Cite
|
Sign up to set email alerts
|

The effects of curcumin on the invasiveness of prostate cancer in vitro and in vivo

Abstract: Curcumin has become a focus of interest with regard to its antitumor effects in prostate cancer; however, the effects of this agent on invasion and metastasis remain less well understood. Matrix metalloproteinases (MMPs) are important prerequisite for tumor invasion and metastasis. In this study, we evaluated the effects of curcumin on prostate cancer cells (DU-145) invasion in both in vitro and in vivo. We utilized zymography and ELISA in order to determine the MMP-2 and MMP-9 activity. Matrigel invasion assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 14 publications
4
97
0
2
Order By: Relevance
“…Additionally, they found that at increasing concentrations of curcumin (1, 5, 10 μg/ml), the invasive characteristics of cultured DU145 cells were blocked in a dose-dependent manner, with highest concentration inhibiting invasion by 71%. While, the 30-μM curcumin concentration used in our study was similar to the highest and most effective dose used in the study of Hong et al (10 μg/ml or ~27 μM), we observed the effect of curcumin in our study was far more subtle (19). We found that curcumin (30 μM; 18 h) blocked the invasive characteristics of PC-3 cells by 23% of control cells.…”
Section: Discussionsupporting
confidence: 27%
See 1 more Smart Citation
“…Additionally, they found that at increasing concentrations of curcumin (1, 5, 10 μg/ml), the invasive characteristics of cultured DU145 cells were blocked in a dose-dependent manner, with highest concentration inhibiting invasion by 71%. While, the 30-μM curcumin concentration used in our study was similar to the highest and most effective dose used in the study of Hong et al (10 μg/ml or ~27 μM), we observed the effect of curcumin in our study was far more subtle (19). We found that curcumin (30 μM; 18 h) blocked the invasive characteristics of PC-3 cells by 23% of control cells.…”
Section: Discussionsupporting
confidence: 27%
“…This finding is supported by other published reports. Hong et al for example, showed that curcumin decreased PCa tumor and metastasis burden of DU145 xenografts implanted into SCID mice, in part through the inhibition of MMP proteins after 24-h exposure (19). Additionally, they found that at increasing concentrations of curcumin (1, 5, 10 μg/ml), the invasive characteristics of cultured DU145 cells were blocked in a dose-dependent manner, with highest concentration inhibiting invasion by 71%.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, curcumin has been observed to induce a marked reduction in MMP-2 and MMP-9 activity in tumor-bearing sites. A previous study demonstrated significantly fewer metastatic nodules in a curcumin-treated group compared with the untreated group (75).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Accordingly, several studies demonstrated a correlation between high invasiveness and decreased TIMP-1- (Khokha et al, 1989;Chan et al, 2005) or increased MMP-2 expression (Mori et al, 2004;Choi et al, 2005). Conversely, the antiinvasive action of several anticarcinogenic substances has been associated with elevated TIMP-1 (Khokha et al, 1992;Park et al, 2005) or diminished MMP-2 levels (Park et al, 2005;Hong et al, 2006).…”
mentioning
confidence: 99%